Enhancement of AC System Stability using Artificial Neural Network Based HVDC Controls - Nagu Nayak Bhukya; Ramana Rao P.V.; Sydulu M. (International Journal of Electrical and Computer Engineering (IJECE), 2013)
In this paper, investigation is carried out for the improvement of power system stability by utilizing auxiliary controls for controlling HVDC power flow. The current controller model and the line dynamics are considered in the stability analysis. Transient stability analysis is done on a multi-machine system, where, a neural network controller is developed to improve the stability of the power system and to improve the response time of the controller to the changing conditions in power system. The results show the application of the neural network controller in AC-DC power systems and case studied at different fault locations.DOI:http://dx.doi.org/10.11591/ijece.v3i4.2590